Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1093/cvr/cvw075
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular matrix remodelling in response to venous hypertension: proteomics of human varicose veins

Abstract: AimsExtracellular matrix remodelling has been implicated in a number of vascular conditions, including venous hypertension and varicose veins. However, to date, no systematic analysis of matrix remodelling in human veins has been performed.Methods and resultsTo understand the consequences of venous hypertension, normal and varicose veins were evaluated using proteomics approaches targeting the extracellular matrix. Varicose saphenous veins removed during phlebectomy and normal saphenous veins obtained during c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 41 publications
1
53
0
9
Order By: Relevance
“…In the deep proteomic study of mouse lung ECM by Schiller et al [16], only 53 of a total 264 matrisome-associated proteins were found to be enriched in the insoluble fraction after quantitative detergent solubility profiling. Similarly, in a study of the human ventricle ECM performed by Barallobre-Barreiro et al [46], a higher abundance of matrisome-associated proteins such as S100 proteins or ECM peptidases was found in the soluble fraction. Our data highlight that in-depth proteomic analysis of non-enriched samples is currently the best available tool for the analysis of this class of proteins; however, further development of new enrichment strategies to better isolate matrisome-associated proteins with improved sequence coverage is necessary.…”
Section: Resultsmentioning
confidence: 67%
“…In the deep proteomic study of mouse lung ECM by Schiller et al [16], only 53 of a total 264 matrisome-associated proteins were found to be enriched in the insoluble fraction after quantitative detergent solubility profiling. Similarly, in a study of the human ventricle ECM performed by Barallobre-Barreiro et al [46], a higher abundance of matrisome-associated proteins such as S100 proteins or ECM peptidases was found in the soluble fraction. Our data highlight that in-depth proteomic analysis of non-enriched samples is currently the best available tool for the analysis of this class of proteins; however, further development of new enrichment strategies to better isolate matrisome-associated proteins with improved sequence coverage is necessary.…”
Section: Resultsmentioning
confidence: 67%
“…The two time points of 30 and 60 days did not differ significantly when considering all categories of improvement ( P = 0.29). However, results suggest a tendency of improvement between 30 and 60 days which might be due to the prolonged time necessary for remodelling of initial pathological changes in the extracellular matrix in varicose veins .…”
Section: Resultsmentioning
confidence: 92%
“…Over the past years our group has focused on ECM remodelling in cardiac 2 , 52 , 60 , 61 and vascular tissues 3 , 4 , 57 , 59 using proteomics. In a previous review, we highlighted the potential of proteomics when applied to systems biology 62 .…”
Section: Extraction Of Ecm Proteinsmentioning
confidence: 99%
“…demonstrated in a study that also included ECM biomarkers of fibrosis. Moreover, targeted proteomics constitutes a robust method to validate findings obtained from discovery experiments ( Figure 4 ) 3 Figure 4MS strategies for ECM characterisation.…”
Section: Targeted Proteomicsmentioning
confidence: 99%
See 1 more Smart Citation